A review of peripheral nerve blocks for cesarean delivery analgesia. Issue 1 (January 2020) - Mitchell, Kelsey D; Smith, C Tyler; Mechling, Courtney; Wessel, Charles B; Orebaugh, Steven; Lim, Grace
Abstract : Peripheral nerve blocks have a unique role in postcesarean delivery multimodal analgesia regimens. In this review article, options for peripheral nerve blocks for cesarean delivery analgesia will be reviewed, specifically paravertebral, transversus abdominis plane, quadratus lumborum, iliohypogastric and ilioinguinal, erector spinae, and continuous wound infiltration blocks. Anatomy, existing literature evidence, and specific areas in need of future research will be assessed. Considerations for local anesthetic toxicity, and for informed consent for these modalities in the context of emergency cesarean deliveries, will be presented.